Digital analysis of facial landmarks in determining facial midline among Punjabi population - Nirmal Kurian; Nitasha Gandhi; Angleena Y Daniel; Vinaya Susan Varghese; Smitha Daniel; Surbhi Mehdiratta (Wolters Kluwer Medknow Publications, 2018)
Introduction: Prosthodontic rehabilitation aims to achieve the best possible facial esthetic appearance for a patient. Attaining facial symmetry forms the basic element for esthetics, and knowledge of the midline of face will result in a better understanding of dentofacial esthetics. Currently, there are no guidelines that direct the choice of specific anatomic landmarks to determine the midline of the face or mouth. Most clinicians choose one specific anatomic landmark and an imaginary line passing through it. Thus, the clinician is left with no established guidelines to determine facial midline. Objective: The purpose of the study is to digitally determine the relationship of facial landmarks with midline of face and formulate a guideline for choosing anatomic landmark among Punjabi population. Materials and Methods: Three commonly used anatomic landmarks, namely nasion, tip of the nose, and tip of the philtrum, were marked clinically on 100 participants (age range: 21-45 years). Frontal full-face digital images of the participants in smile were then made under standardized conditions. Midline analysis was carried out digitally using an image analyzing software. The entire process of midline analysis was done by a single observer and repeated twice. Reliability analysis and one-sample t-tests were conducted. Results: The results indicated that each of the four landmarks deviated uniquely and significantly (P < 0.001) from the midlines of the face as well as the mouth. Conclusions: Within the limitations of the study, the hierarchy of anatomic landmarks closest to the midline of the face in smile was as follows: (1) Intercommissural midlines, (2) Tip of philtrum, (3) Nasion, (4) Tip of the nose, and (5) Dental midlines. The hierarchy of anatomical landmarks closest to the intercommissural/mouth midline was: (1) Tip of philtrum, (2) Tip of the nose, (3) Nasion, and (4) dental midline.